PROPAGANDA: AHOK TIDAK PANTAS JADI GUBERNUR - Adi Prakosa (Populis : Jurnal Sosial dan Humaniora, 2018)
Independent press and objective news are the rules. But on the news "Chairman of DPW Gerindra DKI: Ahok Enggak Indonesia Banget", in news published by Republika.co.id on Wednesday, July 27, 2016 edition, normative things that are violated. This is the reason to review the discourse submitted by Republika on line. The research method uses discourse analysis of Fairlcloud model. The theory used as a reference is Critical Theory. The results show that the news reviewed represents Ahok inappropriate to be governor. There are propaganda techniques applied, namely the name  calling, card staking, and testimonials.Keywords: press, news, discourse analysis